The Effect of Implementing K3 (Occupational Safety and Health) on Employee Performance of PT OHM Elektronik Jababeka Cikarang - Silvia Hilwiatun Nisfi; Boma Jonaldy Tanjung; Sri Wahyuni (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Background: The high risk of accidents in the electronics industry demands an effective Occupational Safety and Health (OSH) system. Objective: Measure the influence of behavior-based training, incident reporting systems, and adaptive evaluation on productivity, discipline, and quality of work. Method: Associative quantitative design with purposive sampling of 30 production operators. Instrument: Likert scale closed questionnaire based on five OSH indicators and five performance indicators. Analysis techniques: Descriptive statistics, Shapiro–Wilk normality test, Glejser heteroscedasticity test, simple linear regression, t-test, and coefficient of determination (R²). Result: Regression equation Y=2.504+0.937X+eY=2,504+0,937X+e; OSH had a significant positive effect (t=15,399; p<0.001) and explained 89.4% of performance variation. Conclusions: Improved OSH implementation promotes employee performance; companies are advised to maintain behaviour-based training and adaptive safety evaluation.a